Representasi Pengetahuan Sistem Pakar Menggunakan Struktur Data Redis - Sammir, Haddad; Hamdi, Khairil; Sunaryo, Budi (Ikatan Ahli Informatika Indonesia, 2024)
This research discusses knowledge representation in expert systems using the Redis data structure, with a focus on the knowledge-based inference process. Inference in an expert system involves comparing existing facts with an existing database. When the elements in the rule match the database, the rule is considered TRUE and processed further in the database. For efficiency and speed in the inference process, this research utilizes the Redis data structure, especially the